2007
DOI: 10.2478/s11658-006-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

The molecular diversity of different isolates of Beauveria bassiana (Bals.) Vuill. as assessed using intermicrosatellites (ISSRs)

Abstract: Inter-microsatellite PCR (ISSR-PCR) markers were used to identify and to examine the genetic diversity of eleven Beauveria bassiana isolates with different geographic origins. The variability and the phylogenetic relationships between the eleven strains were analyzed using 172 ISSR-PCR markers. A high level of polymorphism (near 80%) was found using these molecular markers. Seven different isolates showed exclusive bands, and ISSR primer 873 was able to distinguish between all the strains. The dendrogram obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The authors observed the formation of three groups and a slight variation among the populations (18.5 and 19.35%), and there was no association between genetic diversity and the collection sites for the different isolates. ISSR markers detected a high level of polymorphism for isolates of B. bassiana, which were grouped according to geographic origin, but there was no clear correlation between those isolates and their insect hosts (Aquino de Muro et al, 2005;Wang et al, 2005;Estrada et al, 2007) and for isolates of E. muscae (Lihme et al, 2009) bassiana isolates, genetic similarity that ranged from 0.651 to 0.972. Estrada et al (2007) studied 11 isolates and found that seven isolates showed exclusive bands and that ISSR primer 873 was able to distinguish all the isolates.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors observed the formation of three groups and a slight variation among the populations (18.5 and 19.35%), and there was no association between genetic diversity and the collection sites for the different isolates. ISSR markers detected a high level of polymorphism for isolates of B. bassiana, which were grouped according to geographic origin, but there was no clear correlation between those isolates and their insect hosts (Aquino de Muro et al, 2005;Wang et al, 2005;Estrada et al, 2007) and for isolates of E. muscae (Lihme et al, 2009) bassiana isolates, genetic similarity that ranged from 0.651 to 0.972. Estrada et al (2007) studied 11 isolates and found that seven isolates showed exclusive bands and that ISSR primer 873 was able to distinguish all the isolates.…”
Section: Discussionmentioning
confidence: 96%
“…ISSR markers detected a high level of polymorphism for isolates of B. bassiana, which were grouped according to geographic origin, but there was no clear correlation between those isolates and their insect hosts (Aquino de Muro et al, 2005;Wang et al, 2005;Estrada et al, 2007) and for isolates of E. muscae (Lihme et al, 2009) bassiana isolates, genetic similarity that ranged from 0.651 to 0.972. Estrada et al (2007) studied 11 isolates and found that seven isolates showed exclusive bands and that ISSR primer 873 was able to distinguish all the isolates. Studies with respect to introns of group I have sought to identify them and check for polymorphism among the isolates of M. anisopliae by way of phylogenetic analysis (Mavridou et al, 2000;Márquez et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Secondly, the effective multilocus markers used for diversity analysis, fingerprinting and genome mapping (Nghia et al 2008) are easy to employ and are highly reproducible compared with other technique, such as RAPD, and no prior sequence knowledge is required (Goldwin et al 1997 (Kauserud and Schumacher 2003), Ustilago spp. (Menzies et al 2003), Serpula lacrymans (Kauserud 2003) and Beauveria bassiana (Elena Estrada et al 2007). ISSRs have been used to characterize genetic variation within fungi but, to date, not with the smut fungi and T. controversa.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent publications have shown that B. bassiana isolates are very genetically variable (Aquino de Muro et al 2003Estrada et al 2007;Ormond 2007), and concomittantly highly phenotypically variable in parameters such as virulence (Bidochka et al 2002;Devi and Rao 2006;Talaei-Hassanloui et al 2006). The natural enemy escape hypothesis is often used as an explanation for the rapid establishment and proliferation of an invasive alien species; the geographical displacement of the species results in escape from predators and parasites and so gives the invading species an advantage over native species that are attacked by a suite of indigenous natural enemies (e.g.…”
Section: Discussionmentioning
confidence: 99%